ASSA14-03-18 Contribution of Homeostatic Chemokines CCL19 and CCL21 and their Receptor CCR7 to Coronary Artery Disease. (1st December 2014) - Cai, W; Tao, J; Zhang, X; Tian, X; Liu, T; Feng, X; Bai, J; Yan, C; Han, Y
Abstract : Background: Aim to identify the role of the homeostatic chemokines CCL19 and CCL21 and their common receptor CCR7 in atherogenesis, and to study the relationships between CCL19, CCL21 and CCR7 gene variants and coronary artery disease (CAD) in a Chinese Han population. Methods: Collect atherosclerosis and normal human coronary arteries, and use the immunohistochemical staining to detect the experssion of CCL19, CCL21 and CCR7. Detect the role of CCL19, CCL21 and CCR7 in monocytes adhereing and migrating to the Human umbilical vein endothelial cells (HUVECs). Ten tagSNPs were retrieved from the Hapmap database for Han population samples in the CCL19, CCL21 and CCR7 genes and 2.0 KB regions on each side. In 1746 cases of the north group and 700 cases of the south group, the SNP genotypes were detected by polymerase chain reaction-direct sequencing method and the associations between every SNP genotypes and alleles and coronary heart disease, and associations between plasma CCL19 and CCL21 level and SNP genotypes were analysised. Results: Immunohistochemical analysis of samples with atherosclerosis of various stages showed increased CCL19, CCL21 and CCR7 expression in atherosclerotic coronary plaques compared with non-atherosclerotic controls. Expression levels increased in positive correlation with the levels of the coronary lesions. Cell adhesion assays confirmed that CCL19 promoted monocyte adhesion, which was induced by CCR7, to human umbilical vein endothelial cells (HUVECs), and the increased adhesion could be partially antagonised by atorvastatin. The associations between genetic variants of CCL19, CCL21, CCR7 and CAD in a Chinese Han population were determined by matrix-assisted laser desorption/ionisation time-of-flight mass spectrometry. The following single nucleotide polymorphisms were associated with CAD: CCL19 rs2227302, CCL21 rs2812377, and CCR7 rs588019. Individuals with the CCL19 rs2227302 T allele or CCL21 rs2812377 G allele had higher plasma CCL19 levels than those with C/C genotype, and higher CCL21 levels than those with T/T genotype in both case and control subjects. Conclusions: CCL19/CCL21-CCR7 is a novel homeostatic chemokine system that modulates human monocyte adhesion and migration, promoting atherogenesis. It is associated with CAD risk in Chinese Han individuals. These data suggest that the CCL19/CCL21-CCR7 axis plays an important role in atherosclerosis progression.